Long‐Term Contrast Echocardiography and Clinical Follow‐Up after Percutaneous Closure of Patent Foramen Ovale Using Two Different Atrial Septal Occluder Devices. (24th June 2016) - Scalise, Filippo; Auguadro, Carla; Sorropago, Giovanni; Sorropago, Antonio; Novelli, Eugenio; Finizio, Marica; Specchia, Giuseppe
Abstract : Introduction: Percutaneous patent foramen ovale (PFO) closure by means of a septal occluder device (SOD) is a well‐known therapeutic strategy for the secondary prevention of paradoxical embolic neurological events. The aim of this study was to provide long‐term echocardiographic and clinical follow‐up data on patients who had undergone percutaneous PFO closure with 2 different SOD. Methods: We selected 2 groups of patients treated with 2 different SOD: Group A: 52 patients with an Amplatzer ® PFO Occluder and Group B: 49 patients with a Figulla Flex ® device. All patients underwent follow‐up Bubble Test Transthoracic Echocardiography (BTTE) and clinical examination. The results were compared with those recently reported in a group of patients with similar characteristics, but that had been treated conservatively, which acted as a control group. Results: The mean follow‐up after PFO closure was 53 months. The Amplatzer ® PFO Occluder and the Figulla Flex were used in 52 (51.5%) and 49 (48.5%) of patients, respectively. We found no significant difference in the rate of effective PFO closure between the devices: Amplatzer 91.4%, Figulla 93.9% (P = 0.71). One patient (1.0%) suffered a recurrent neurologic event. BTTE was positive (BTTE+) in 8 patients (8%), 5 with an Amplatzer, and 3 with a Figulla device (P = 0.516). Only 1 patient with BTTE+ had a recurrent TIA (12.5%). No significant relationship was found between device dimensions and BTTE+ (P = 0.062). In the control group (163 patients), the recurrence of neurologic events was 9.2% (15 events), that was significantly higher in respect to the patients who had undergone percutaneous closure of the PFO. Conclusions: Percutaneous PFO closure was associated with a remarkably low risk of recurrent embolic neurological events, and no long‐term device‐related major complications. No statistically significant difference emerged between the 2 different SODs regarding BTTE positivity. Long‐term follow‐up showed that the recurrence of neurological events has been significantly higher in the group treated in a conservative way.